Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

PLease HELP HELP HELP HELP!
(I SUCK AT MATH! NOT MY FAVE SUBJECT)


PLease HELP HELP HELP HELP I SUCK AT MATH NOT MY FAVE SUBJECT class=

Sagot :

Answer:

y^2(y^4)=y^6

(2y)^2=4y^2

(y/4)^2=y^2/16

2(y^3)^3=2y^9

Step-by-step explanation:

Answers:

[tex]y^2(y^4) = \boldsymbol{y^6}\\\\(2y)^2 = \boldsymbol{4y^2}\\\\(y/4)^2 = \boldsymbol{y^2/16}\\\\2(y^3)^3 = \boldsymbol{2y^9}\\\\[/tex]

===============================================

Explanation:

For the first expression, we use the rule that [tex]a^b*a^c = a^{b+c}[/tex]. We add the exponents when multiplying exponentials of the same base. So, [tex]y^2*y^4 = y^{2+4} = \boldsymbol{y^6}[/tex]

-----------

In the second expression, we can expand out [tex](2y)^2[/tex] into [tex](2y)*(2y)[/tex]. The coefficients 2 and 2 multiply to 2*2 = 4 as the final coefficient. The y terms multiply to [tex]y*y = y^2[/tex]. So overall, that's how [tex](2y)^2 = \boldsymbol{4y^2}[/tex]

-----------

We use the same idea for the third expression. We'll have two copies of y/4 multiplied together to end up with [tex]\boldsymbol{y^2/16}[/tex]. We have [tex]y^2[/tex] in the numerator and 16 in the denominator.

-----------

For the fourth expression, we can use the rule that [tex](a^b)^c = a^{b*c}[/tex]. In other words, if we raised [tex]a^b[/tex] to some other exponent c, then it's the same as writing [tex]a^{b*c}[/tex]. We multiply the exponents.

The exponents in this case are 3 and 3 which multiply to 9. The 2 is then tacked up front to get [tex]\boldsymbol{2y^9}[/tex]